Diploma Withholding by Companies in the Perspective of Constitutional Rights to Education and Employment : A Case Study in Surabaya - Syaidi, Ridwan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study examines the practice of diploma withholding by companies in Indonesia from the perspective of constitutional rights to education and employment. Diploma withholding, often imposed as a means of ensuring employee compliance, raises fundamental legal issues as it involves the misuse of personal documents containing private data and potentially violates workers’ constitutional rights guaranteed under Article 28D paragraph (2) and Article 31 of the 1945 Constitution. Using a qualitative normative legal research method with statutory and case approach, this study analyzes the legal implications of such practices in relation to labor law, the Law on Personal Data Protection, and constitutional guarantees. The findings show that diploma withholding not only undermines legal certainty and fair treatment in employment relations but also contradicts the principle of human dignity protected under constitutional law. The study concludes that diploma withholding should be considered a violation of constitutional rights, requiring stronger regulatory enforcement and constitutional awareness by both state authorities and corporate actors.